2020
DOI: 10.3390/biomedicines8120546
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Steatohepatitis Decreases Microsomal Liver Function in the Absence of Fibrosis

Abstract: The incidence of non-alcoholic fatty liver disease (NAFLD) is rising across the globe, with the presence of steatohepatitis leading to a more aggressive clinical course. Currently, the diagnosis of non-alcoholic steatohepatitis (NASH) is based on histology, though with the high prevalence of NAFLD, a non-invasive method is needed. The 13C-aminopyrine breath test (ABT) evaluates the microsomal liver function and could be a potential candidate. We aimed to evaluate a potential change in liver function in NASH pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Here, labelled C13 urea is administered to patients, and then their exhaled breath is collected, where the isotope-labelled carbon dioxide is measured. Other C13 breath tests, such as the C13 aminopyrine breath test, have also been used to examine liver diseases [ 19 , 20 ]; however, C13 implementations are outside the scope of the present review since they are not based on VOC analysis. The current review focuses on endogenously formed compounds that have been connected with liver impairment, among which are nitrogen derivates [ 4 ], ketones [ 21 ], alkanes [ 21 ], sulphur derivates [ 1 ], and alcohols [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, labelled C13 urea is administered to patients, and then their exhaled breath is collected, where the isotope-labelled carbon dioxide is measured. Other C13 breath tests, such as the C13 aminopyrine breath test, have also been used to examine liver diseases [ 19 , 20 ]; however, C13 implementations are outside the scope of the present review since they are not based on VOC analysis. The current review focuses on endogenously formed compounds that have been connected with liver impairment, among which are nitrogen derivates [ 4 ], ketones [ 21 ], alkanes [ 21 ], sulphur derivates [ 1 ], and alcohols [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 13C-aminopyrine breath test (ABT) evaluates the microsomal liver function and could be a potential candidate to allow the discrimination between simple steatosis to NASH. Using this approach, in this Special Issue, Verlinden et al [ 5 ] aimed to evaluate a potential change in liver function in NASH patients and to assess the diagnostic power to detect NASH. They demonstrated that the microsomal liver function of patients with NASH is significantly decreased, even in the absence of fibrosis.…”
mentioning
confidence: 99%